Integrated multiresponse parameter and tolerance design with model parameter uncertainty. (17th November 2019) - Han, Yunxia; Ma, Yizhong; Ouyang, Linhan; Wang, Jianjun; Tu, Yiliu
Abstract: Integrated parameter and tolerance design is a cost‐effective method to multiresponse quality improvement. However, previous methods usually ignore model parameter uncertainty, dispersion effect, or correlation among responses. This may lead to the obtained optimal solutions far from the true optimal values of parameters and tolerances. To address the problem, a novel integrated parameter and tolerance design method is proposed to solve correlated multiple response problems under consideration of model parameter uncertainty, the location and dispersion effects of the quality loss, and the tolerance costs simultaneously. As there usually exists uncertainty in the quality loss and tolerance costs, multiobjective optimization is adopted to seek for the robust optimal solutions. The effectiveness and robustness of the proposed method are illustrated with a practical example and a random simulation example. The results show that the proposed method provides more reasonable results in quality improvement and cost reduction than those of the existing methods.